PET-CT and Occupational Exposure in Oncological Patients - Mikhail Osipov; Andrey Vazhenin; Anna Kuznetsova; Irina Aksenova; Daria Vazhenina; Mikhail Sokolnikov (Ital Publication, 2020)
The paper describes the results of retrospective epidemiological study on low dose effects of diagnostic radiation exposure to humans. The data used in the study has been collected from archives of Chelyabinsk Regional Clinical Center of Oncology and Nuclear Medicine during the project for creating the local electronic database of Ozyorsk patients examined with computed tomography (CTDB). The study group consisted of oncological patients who have received positron-emission computed tomography (PET-CT). All patients in the study group were residents of Ozyorsk - the town in South Ural where the "Mayak" production association, also known as 1st Russian nuclear enterprise is located. The main purpose of the study was to understand whether the number of PET-CT scans, as well as other radiation risk factors influences the mortality in the exposed group. The follow-up period started in 2010 since the first PET-CT scans has been performed, and ended in June, 2019. Radiation dose for oncological patients exposed to PET-CT has been compared with the cumulative dose from occupational exposure. Vital status and cause of death of patients who died to the end of follow-up has been established using the data of National Cancer Registry in part located in the Chelyabinsk Regional Clinical Center of Oncology and Nuclear Medicine. Cancer mortality has been analysed depending on age of patient, sex, number of PET-CT examinations, and presence of occupational exposure, using the logistic regression model. Main radiation risk factors influencing cancer mortality has been established.